Activity of different AlCl3-based electrolytes for the electrically rechargeable aluminium-air battery. (1st June 2018) - Bogolowski, Nicky; Drillet, Jean-Francois
Abstract: Feasibility of AlCl3 -based acetamide and urea deep-eutectic solvents as well as EMImCl ionic liquid as electrolyte for rechargeable Aluminium/air cell was evaluated under half-cell and full-cell conditions under ultra-dry atmosphere. Half-cell measurements revealed satisfactory activity of all studied electrolytes for Aluminium stripping/deposition with a certain disparity in overpotential and stability. Evaluation at Pt and more especially determination of ORR onset potential was not straightforward. Nonetheless, all systems exhibited a suitable activity and cycling ability under full-cell conditions. Current and energy efficiencies of 84% and 56% were calculated during first 15 charge/discharge Al/air cycles at 100 μA cm −2 for 3 h each in acetamide electrolyte, respectively. Since theoretical reversible electrolyte capacity was evaluated to approximately 28 mAh, only 2.5% of theoretical capacity was able to be cycled. Graphical abstract: Image 1 Highlights: Activities of different AlCl3 -based ILs and deep eutectic solvents for Al deposition/stripping and OER/ORR are compared. Pyrolytic graphite was used as substrate for Al deposition. Current and energy efficiency of 84 and 56% for Al/air full-cell with acetamide+ACl3 during the first 15 cycles. First electrically rechargeable Al/air cell with acetamide.